Modern families : parents and children in new family forms - Golombok, Susan (Cambridge ; New York : Cambridge University Press, 2015)
"Modern Families brings together research on parenting and child development in new family forms including lesbian mother families, gay father families, families headed by single mothers by choice and families created by assisted reproductive technologies such as in vitro fertilisation (IVF), egg donation, sperm donation, embryo donation and surrogacy. This research is examined in the context of the issues and concerns that have been raised regarding these families. The findings not only contest popular myths and assumptions about the social and psychological consequences for children of being raised in new family forms but also challenge well-established theories of child development that are founded upon the supremacy of the traditional family. It is argued that the quality of family relationships and the wider social environment are more influential in children's psychological development than are the number, gender, sexual orientation, or biological relatedness of their parents or the method of their conception"--
"The popular American sitcom Modern Family, featuring the trials, tribulations and, in many ways, very ordinary lives of three related contemporary families, including Jay, a middle-aged father who is remarried to a much younger Columbian woman who has a son from a previous marriage, Jay's daughter and her traditional family with a hands-on father and their three children, and Jay's gay son, his male partner and their adopted Vietnamese daughter, highlights the diverse ways in which families are formed today. Although Modern Family is a parody of present-day family life, the reality is even more extraordinary"--
Machine generated contents note: 1. Introduction; 2. Lesbian mother families; 3. 'Test-tube' baby families; 4. Donor conception families; 5. Surrogacy families; 6. Solo mother families; 7. Gay father families; 8. Conclusions.
Includes bibliographical references (pages 218-260) and index.
Keywords: Parenting; Child development; Families; Mother and child; PSYCHOLOGY / Developmental / General